Exposure‐Safety Analyses of Talazoparib in Patients With Advanced Breast Cancer and Germline BRCA1/2 Mutations in the EMBRACA and ABRAZO Trials. (28th May 2020) - Elmeliegy, Mohamed; Yu, Yanke; Litton, Jennifer K.; Czibere, Akos; Wilson, Gary G.; Tudor, Iulia Cristina; Zheng, Jenny; Wang, Diane D.
Abstract: Poly(ADP‐ribose) polymerase inhibitors, such as talazoparib, may affect hematopoiesis. This analysis characterized the relationship between talazoparib exposure and the most common grade ≥ 3 hematopoietic adverse events (AEs) leading to dose modification in the phase 2 (ABRAZO) and phase 3 (EMBRACA) trials. The relationship between time‐varying average talazoparib concentration (Cavg, t ), along with other baseline variables, and grade ≥ 3 anemia, thrombocytopenia, and neutropenia were evaluated both by graphical examination and using univariate and multivariate Cox proportional hazard models. The results indicated that higher Cavg, t was associated with a higher risk of anemia and thrombocytopenia. A trend toward an association between higher Cavg, t and neutropenia was observed, although not statistically significant. Higher risk of all tested safety end points was associated with lower baseline hemoglobin. Higher risk of neutropenia was associated with lower baseline absolute neutrophil count and lower body weight. These findings support the proposed management of AEs through talazoparib dosing modification.